Problems of distribution and marketing of agricultural produce; a study of the role of women in the Kumasi Central Market - Maputsoe, Nthoateng Cornelia (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Science in Development Planning and Management.